THE GAP BETWEEN LEARNING NEEDS AND ITS IMPLEMENTATION IN ENGLISH FOR HOSPITALITY SPECIFIC PURPOSES PROGRAM - Dian Kardijan (University of Kuningan, 2017)
This study is to reveal the gap between the English language communicative competence required by students of the hospitality department and English learning program provided at state of Vocational High School 1 Tasikmalaya, Indonesia, drawing through qualitative evaluation approach, including semi-structured interviews and observations. It explores how learning needs is implemented in teaching-learning process and the respondents description, what they saw and what they felt. Findings show inconsistency between learning needs in enrichment students English communicative competence and teaching-learning process. This prompts a re-instructional design of English learning for hospitality specific purposes program at this department currently. It provides to support of graduating required at hospitality industry workplace. Lead of recommendations, in terms of both the instructional design including materials development, teaching method usage and the professional development of ESP teachers, to address an understanding of the gap identified, so that students will enable to communicate more effectively with the English, in such contexts graduates can hire at the hospitality industry workplace.Keywords: learning needs, pre-vocational English field, authentic materials and teaching methods